BUSINESS EDUCATION IN THE CONDITIONS OF GLOBAL COMPETITION - Ахновская, Инна; Болгов, Владислав (SWorldJournal, 2020)
Introduction. In the conditions of global competition the problem of creation of modern model of business education is actualized. The purpose of of the article is to determine the role and current trends in business education in global competition.Resu